Application Research of Computational Fluid Mechanics Based on CNKI Database. (July 2020) - Yan, Li
Abstract: Based on the China Knowledge Network Database (CNKI), a literature measurement analysis of the domestic computational fluid dynamics (CFD) application research was conducted. The results show that from 1973 to 2019, the number of articles published by CFD research has increased significantly year by year. The earliest literature on CFD published in the database was published in 1973, and more than 10 articles have been published annually since 2005. The text-issuing institutions are mainly well-known universities in China, among which Tianjin University has the most. Many masters and doctors in this university obtain degrees through researches related to computational fluid mechanics. CFD theory and software are mainly studied in Engineering technology and basic and applied basic research, and more research has been supported by the National Natural Science Foundation.